George Owen Squier U.S. Army major general, inventor, aviation pioneer, founder of Muzak - Clark, Paul W. 1935-; Lyons, Laurence A. (McFarland, 2014)
"During the 1920s and 30s, Major General George Owen Squier was one of the most famous men in America and abroad, as a scientist, soldier, military strategist, electrical communications expert and inventor, aeronautical pioneer, diplomat, and philanthropist. He equipped American forces with modern communications. Despite his many achievements, no biography of George Squier has, before now, been published"--
Includes bibliographical references and index
Early Life and West Point -- Soldier-Scientist -- An Electrical Laboratory -- Soldier-Entrepreneur -- The Philippine Cables -- Founding of the Signal School -- Origins of Army Aviation -- Radio Over Telephone Lines -- Science and Syndicate -- Secret Missions -- The Biggest Thing of the War -- New Weapons -- Science Joins the Army -- Voice-Commanded Squadrons -- Retirement Years and Legacy -- Appendix: Technical Information
Keywords: Squier, George Owen / 1865-1934; Squier, George Owen -- 1865-1934; United States / Army / Officers / Biography; Military engineers / United States / Biography; Aeronautical engineers / United States / Biography; Generals / United States / Biography; Inventors / United States / Biography; Ingenieur; USA; Biografie